2003
DOI: 10.1046/j.1432-1033.2003.03721.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose sensing in the intestinal epithelium

Abstract: Dietary sugars regulate expression of the intestinal Na + / glucose cotransporter, SGLT1, in many species. Using sheep intestine as a model, we showed that lumenal monosaccharides, both metabolisable and nonmetabolisable, regulate SGLT1 expression. This regulation occurs not only at the level of transcription, but also at the post-transcriptional level. Introduction of D-glucose and some D-glucose analogues into ruminant sheep intestine resulted in > 50-fold enhancement of SGLT1 expression. We aimed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 35 publications
2
103
1
5
Order By: Relevance
“…Vagal afferents from the gastrointestinal tract project to the hypothalamus (4,31) and are, among others, important for blood glucose regulation (3,38). The gastrointestinal tract features glucoreceptors and osmoreceptors (13,25), as well as sweet-taste receptors (12). Intestinal glucoreceptors take part in glucoregulation by mediating nervous control of insulin release via the vagus nerve (26) and glucoseinduced increases in pancreatic islet blood flow (6).…”
Section: Discussionmentioning
confidence: 99%
“…Vagal afferents from the gastrointestinal tract project to the hypothalamus (4,31) and are, among others, important for blood glucose regulation (3,38). The gastrointestinal tract features glucoreceptors and osmoreceptors (13,25), as well as sweet-taste receptors (12). Intestinal glucoreceptors take part in glucoregulation by mediating nervous control of insulin release via the vagus nerve (26) and glucoseinduced increases in pancreatic islet blood flow (6).…”
Section: Discussionmentioning
confidence: 99%
“…We could suggest that the GLUT2-dependent enteric glucose absorption is not a major regulatory mechanism for enteric glucose sensing. A complementary set of evidence has also suggested that carbohydrate receptors exist in the lumen of the intestine (Dyer et al, 2003a;Dyer et al, 2003b;Dyer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…SGLT1 protein, however, was present on the luminal membrane of all of the villus enterocytes in mouse intestine ( Fig. 3H) (6,16). To investigate the colocalization of T1R taste receptor subunits and G␣ gust , we used serial sections of wax-embedded mouse ( Fig.…”
Section: Regulation Of Intestinal Sglt1 Expression In Wild-type and Kmentioning
confidence: 99%
“…Although the gut epithelium senses luminal sugars and modulates its glucose absorptive capacity accordingly, the nature of the sugar-sensing molecule(s) and downstream events remain unknown. Several studies have shown that in many species expression of the intestinal sodium-dependent glucose transporter 1 (SGLT1) is directly regulated by monosaccharides in the lumen of the gut independently of metabolism and appears to involve a G protein-linked second messenger pathway (2)(3)(4)(5)(6). Furthermore, the addition of membrane-impermeable glucose analogues to the lumen of the intestine stimulates SGLT1 expression, implying that a glucose sensor on luminal membranes is involved (6).…”
mentioning
confidence: 99%